Role of Feature Extraction Techniques : PCA and LDA for Appearance Based Gait Recognition - Annbuselvi, K; Santhi, N; Sivakumar, S (International Journal of Computer Sciences and Engineering, 2025)
Feature extraction is one of the most important step in image pattern recognition. Some sources of difficulty are the presence of irrelevant information and the relativity of a feature set to a particular application. Feature extraction and description are essential components of various computer vision applications. The concept of feature extraction and description refers to the process of identifying points in an image (interested points) that can be used to describe the image’s contents. The One major goal of feature extraction is to increase the accuracy of learned models by compactly extracting prominent features from the input data, while also possibly removing noise and redundancy from the input. Additional objectives include low-dimensional representations for data imagining and compression for the purpose of reducing data storage requirements as well as increasing training and implication speed. The aim of this paper is to report an descriptive study of most popular feature extraction methods PCA and LDA which are generally used in pattern recognition and the role of PCA and LDA in gait feature extraction